Perspective of the Baduy Community in Utilizing Health Services - Bismihayati Bismihayati; Emon Azriadi; Rahmi Putri Wirman; Mila Sari; Serly Mutia Sari; Siska Wardeni; Syafrijon Syafrijon; Eri Barlian; Siti Fatimah; Iswandi Umar (Science and Environmental Journal for Postgraduate, 2023)
A good health service system is an important part of improving health status and is a necessity for everyone. This system will enable the achievement of health development goals in an efficient, efficient, and targeted manner, and will provide effective health services by taking into account the values that exist in society. Sick community most often self-medicate, both in urban and rural areas. The Baduy community are famous for maintaining their unique traditions and lifestyle and avoiding the effects of modernization. They live simply and respect nature. They shun other community and strictly adhere to their customs. They oppose government policies to provide facilities to other parties, such as building education and health centers. As a result, community there use more traditional health services such as dukun and paraji according to their religious beliefs. This activity was carried out through direct observation and interviews with the Baduy community in Kanekes Village, Leuwidamar Sub-district, Lebak Regency, Banten Province. The purpose of this activity was to see how the perspective of the Baduy community in the utilization of health services. From the results of observations and interviews, it can be concluded that the Baduy community, especially the Baduy Dalam, get more health services through traditional medicine, but if they need more intensive care, there is the Cisimeut health center, which is the only community health center in Baduy that allows the Baduy community to get adequate medical care. need medical personnel. However, access to the community health center takes two to three hours.